Peran Budaya, Kepribadian Aparatur, dan Peraturan terhadap Konflik antara Pemerintah Provinsi dengan Pemerintah Kabupaten/Kota serta Implikasinya terhadap Kinerja (Studi Aparatur Pemerintah di Maluku Utara) - Marwan -; Armanu Thoyib; Munawar Ismail; Margono Setiawan (Jurnal Aplikasi Manajemen, 2010)
This research aims at discovering the influence of some antecedent variables, namely apparatus culture, apparatus personality, and regulations, on two endogenous variables of conflict and local government performance during the conflicts between the provincial and regency/city governments in North Maluku. This study employed two research methods. The first was a quantitative data analysis, which served as the primary method, using Structural Equation Model (SEM). The second was a qualitative analysis using an interactive method. The interactive method was carried out with an in-depth study on the interviews with some local figures. Data analysis was done in several stages, i.e.: data collection, data reduction, data display, and data interpretation.The study reveals the following findings. 1) Apparatus culture, apparatus personality, and regulations have a direly and significant impact on the conflict between the local authorities in North Maluku. The relation direction between the three exogenous variables and conflict is negative, which means that low exogenous variables results in more conflicts. 2) The apparatus culture and personality directly and significantly affect government performance. Regulations also directly influence performance, but the influence is not significant. The positive relation direction implies that negative apparatus culture and personality will result in a poor government performance. 3) Conflicts between the local authorities have a direct and significant impact on their performance. The relation between the variables is negative, which means more conflicts will decrease performance.Keywords: Culture, Apparatus, Personality Apparatus, Regulation, Conflict, Performance, Local Autonomy.